(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Scabies is a contagious skin condition caused by a parasitic mite. The outcome is a significant global burden of disease, with around three million cases documented annually. Aalthough those residing in impoverished or overcrowded conditions are considerably more vulnerable to the condition. Young children, the elderly, and anyone with weakened immune systems are at a higher risk of developing scabies. Scabies outbreaks in institutional settings have also been recorded. Scabies not only causes a very itchy rash, but it can also lead to secondary bacterial infections and related complications, as well as social stigma, sadness, sleeplessness, and significant financial difficulties. The main treatment for scabies is topical creams specifically designed to cure the condition. However, in certain cases, oral ivermectin has been shown to be effective. It is recommended that all individuals living in the same household, regardless of whether they exhibit symptoms or not, should have therapy at the same time. Globally, the presence of scabies commonly signifies inadequate living conditions and underscores the necessity for improvements in basic necessities. Healthcare professionals that engage in collaboration with Indigenous people can expand their expertise in detecting and treating scabies and should actively promote the enhancement of living conditions in regions where scabies is prevalent.